Mortality in the Swedish glassworks industry. - Wingren, Gun; Axelson, Olav (Scandinavian Journal of Work, Environment & Health, 1987)
An earlier, relatively small case-referent study has shown an increased risk for glassworks employees to die from stomach cancer, lung cancer, and cardiovascular disorders. This observation suggested an extended study virtually covering the entire glass-producing industry of Sweden. This new study confirmed the earlier results and, furthermore, an excess risk for colon cancer was also identified. No deviation was found in the cancer mortality pattern for all men in the glass-producing area compared to the whole of Sweden. The grouping of glassworks employees according to type of metal consumption at the glassworks showed the excess risks of stomach cancer, colon cancer, and cardiovascular deaths to relate to glassworks with a high consumption of lead, arsenic, antimony, and manganese. However, the strong correlation of these various metal exposures did not permit any successful separation of the effects of the different metals. For cardiovascular mortality, as for cancer, the glassblowers especially suffered from increased risk. Their exposure might, to a great extent, be oral, involving the glassblower's pipe as a ``vector'' for the exposure to various metals.